2016
DOI: 10.1007/s00190-015-0883-4
|View full text |Cite
|
Sign up to set email alerts
|

High-precision positioning of radar scatterers

Abstract: Remote sensing radar satellites cover wide areas and provide spatially dense measurements, with millions of scatterers. Knowledge of the precise position of each radar scatterer is essential to identify the corresponding object and interpret the estimated deformation. The absolute position accuracy of synthetic aperture radar (SAR) scatterers in a 2D radar coordinate system, after compensating for atmosphere and tidal effects, is in the order of centimeters for TerraSAR-X (TSX) spotlight images. However, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 26 publications
1
56
0
Order By: Relevance
“…Previous validation experiments using artificial targets have found that the accuracy of displacement estimates from PSInSAR analysis is at the millimetre level [15,16]. Recent advances have also seen the development of algorithms for absolute positioning of SAR scatterers using stereo SAR images of targets acquired using multiple imaging geometries [17,18]. Common to all these applications is the need for an artificial target with a geodetically known position that has been designed to have a bright and stable response in SAR imagery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous validation experiments using artificial targets have found that the accuracy of displacement estimates from PSInSAR analysis is at the millimetre level [15,16]. Recent advances have also seen the development of algorithms for absolute positioning of SAR scatterers using stereo SAR images of targets acquired using multiple imaging geometries [17,18]. Common to all these applications is the need for an artificial target with a geodetically known position that has been designed to have a bright and stable response in SAR imagery.…”
Section: Introductionmentioning
confidence: 99%
“…The positioning precision is 1–2 m for C‐band data and less than 1 m for X‐band data (Dheenathayalan, Cuenca, Hoogeboom, & Hanssen, ). Using the exact PS locations, reflections from the ground can be separated from those originating from higher level objects, which may show a different deformation behaviour (Dheenathayalan, Small, Schubert, & Hanssen, ). Georeferencing is thus of high importance in the analysis of the results, in particular when the deformation is localised (Chang & Hanssen, ).…”
Section: Characteristics Applicability and Qualitymentioning
confidence: 99%
“…Moreover, recent approaches on estimating deformation in areas with low coherence, and in the absence of sufficient PS appear to be promising (Morishita & Hanssen, 2015a, 2015b. A low PS density can also be overcome by installing in-situ devices, that is, corner reflectors or active transponders, which provide a strong signal in the SAR images resulting in adequate deformation estimates (Dheenathayalan et al, 2016;Mahapatra et al, 2014;Sarabandi & Chiu, 1996).…”
Section: Applicabilitymentioning
confidence: 99%
“…Millimetre per year accuracy can be achieved in deformation trend estimation. Unfortunately the source of the deformation signal is, in general, less accurately known: geolocation estimates of PS-InSAR are known with metres precision at best, depending on the sensor (Dheenathayalan et al, 2016).…”
Section: Ps-insar Deformation Monitoringmentioning
confidence: 99%